Towards sustainable landfill management - Smith, Richard (Cranfield University, 2006)
The UK is reliant on landfill as a waste management option with some 72% w/w of municipal waste landfilled in 2003/04. This thesis advances an argument that landfill, as practised historically and currently, is unsustainable. This thesis demonstrates, specifically, that current legislative aftercare provisions of 30-60 years are inadequate with reference to modelled landfill completion times (the achievement of equilibrium status) of up to 2,000 years. Uniquely, the research quantifies the scale and significance of methane emissions during the early stages (up to 28 months waste age) of landfill operations at 21 UK landfills using a modified flux box. The onset of methanogenesis is quantified for the first time, using a series of in situ monitoring probes installed at one UK landfill site. A significant and novel finding is that the advective flow of landfill gas is preferentially dominated by lateral movement, evidenced here by examination of a predominantly municipal solid waste (MSW) landfill site in Southern England. The direct implications of this finding for the design of landfill gas management systems are discussed. For future landfills, this research has examined a number of UK scenarios in which the gas and leachate characteristics from waste residues going to landfill are modelled to the point of completion or achievement of equilibrium status. This analysis now allows for a comparative assessment of the future performance of landfills. Under these scenarios, completion times can be reduced in some instances {e.g. landfilling of compost and mechanical biological treatment residues) and extended in others (incinerator bottom ash). Problematic contaminants remain; notably arsenic, chromium and lead. Using the research herein, the work describes the application of a landfill gas management hierarchy. In part response to the requirements of the EU Landfill Directive, this provides a science-based framework for operators to maximise protection of the environment and human health from gaseous emissions. The research provides evidence that can be used by landfill managers seeking to maximise landfill collection efficiency. This contributes to regulators managing public and environmental health and is increasingly significant for climate change.
Keywords: landfill; gas; risk; regulation; management; sustainability; waste treatment